Assessment of clinical tear lipid floating time utilizing dynamic fluorescein test - Ithnin, Mohd. Hafidz; Ariffin, Azrin Esmady; Mohd Kamal, Khairidzan (2019)
Purpose: This study was aimed to evaluate the tear lipid floating time (LFT) using dynamic fluorescein test.